RELEVANCE OF LASUNA RASAYANA IN THE MANAGEMENT OF OPHTHALMIC NEURALGIA WITH RESPECT TO VATAPARYAYA- A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2021)
Trigeminal neuralgia, otherwise known as suicidal disease is the severe and recurrent pain in the distribution of one or more branches of Trigeminal nerve. Patient usually presents with sharp electric shock like pain in face or mouth which lasts for seconds to minutes. This condition may lead the patient to a stage of depression and suicidal tendency. In ophthalmic neuralgia V1 branch of trigeminal nerve is affected where the pain can be interpreted as coming from nose, eyes and head in the areas around the scalp. The management involves anticonvulsants, antidepressants and surgical procedures. Vathaparyaya described by Acharyas shows a close similarity with ophthalmic neuralgia in which vitiated Vata causes pain in the areas of eyelashes and eyebrows. The management of Vataparya is given as same as that of the Vatabhishyanda. In present study, it is observed that Ayurvedic management has provided a significant reduction in intensity and frequency of pain.